The Use of Conversation Diary in Enhancing Students’ English Speaking Skill - Prasanti, Ria Anugrah; Muzammil, Lasim; Widiastuti, Oktavia (Journal of Education Reseach and Evaluation, 2020)
This research describes the use of Conversation Diary as a strategy in increasing students’ English speaking skill and discovers the decreasing of students’ anxiety in performing English speaking. This research is done in Classroom Action Research (CAR) within 2 cycles. Each of the cycle is started by assessing classroom problems, and continues with planning, acting, observing, and reflecting. Each cycle has four meetings to accomplish. The participants of this study were 30 students. They got Conversation Diary treatment during eight weeks. Test 1 and test 2 were conducted to get numerical data while interview, observation checklist, and questionnaire were used to get verbal data needed. The finding informed that cycle 1 failed. It was because most of students’ vocabulary and grammar understanding were still low, caused by length and frequency of time which was too short. On the other hand, from verbal information data, it is found that the students’ behaviour has changed. However, cycle 2 is still needed. Cycle 2 showed students’ behaviour were increased. The students’ score test 3 reached minimum score. In conclusion, this study proved that Conversation Diary could improve the students’ speaking skill better and help decreasing the students’ anxiety. With enough length of time, it would gain better result.